Concentration and species diversity of airborne fungi of Dongargarh - K. Sharma, *Dr. (International Multidisciplinary Research Journal, 2011)
Aeromycoflora of Dongargarh was studied with the help of Petriplate method. Total 177 fungal colonies represented 18 fungal types were observed during the present investigation period. Environmental factor play an important role for the distribution of the fungal spores. Out of 18 fungal types, Maximum numbers of fungi were isolated from anamorphic group, moderate from Ascomycotina and Mycelia sterilia and minimum from Zygomycotina. The fungal species were Cladosporium oxysporium, Fusarium Mycelia sterilia, Aspergillus, Penicillium, Curvularia, Cladosporium, Rhizopus ,Trichoderma species were observed. Aspergillus niger (18.08%). While minimum percentage contribution (0.56%) were observed for A.sp. I, A.oryzae and for Fusarium pallidoroseum.